(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This paper examines the philosophical background of four-winged mythological animal figures well known in traditional Balinese architectural art: the winged serpent, the swan, the Garuda, and the winged lion. These animal figures are carved or positioned on the upper sections of various Balinese Hindu sacred buildings. The study employs a hermeneutic method based on the symbolic meanings of each figure, combined with a literature review of the natural characteristics of the animals that inspired these animal figures. Several branches of knowledge serve as analytical approaches in this study, including Hindu cosmology and mythology; the natural characteristics of the Himalaya; the morphology of the four figures; a semiotic approach; comparative studies of similar objects; and Balinese local wisdom. The findings indicate that these four-winged mythological animals possess philosophical backgrounds shaped through syncretization between mythology and the natural characteristics of several animal species from the Himalayan region. These four-winged mythological figures also embody symbolic meanings as guardians of the heavenly realm, as vehicles of the deities, and as entities possessing the combined traits of the animals that form their composite nature. Therefore, it is appropriate that those animal figures are positioned on the upper sections of traditional Balinese buildings.